(untitled) (Revista Archai, 2025)
This paper provides a framework for understanding how nonideal constitutions are better or worse imitations of the ideal constitution. My suggestion is that the nonideal constitutions imitate the skill of the political expert, which includes an epistemic component (their political knowledge) and two teleological components (the benefit to the citizens on the one hand, and the unity of the city on the other). I then show how some constitutions better imitate the political expert’s skill across these dimensions, as higher-ranked constitutions are in a better epistemic condition, better benefit the citizens, and better foster unity in the city than lower-ranked constitutions. A major upshot of my reading will be to show that Plato recognizes the value of some nonideal constitutions while making clear how they still fall short of the ideal.